Implementasi Inter-Regional Input-Output (IRIO) dalam Pemulihan Perekonomian Wilayah akibat Pandemi Covid-19 di Indonesia - Chaterina Dwi Puspita; Wiwik Andriyani Lestari Ningsih (Politeknik Statistika STIS, 2021)
A country's economy can be seen from the linkages of sectors both within its region (intra-regional) and between regions (inter-regional). One of the tools used to describe the flow of goods and services transactions between sectors on intra-regional and inter-regional is the Inter-Regional Input-Output (IRIO) Table. In the implementation of IRIO, this study aims to analyze the impact of changes in final consumption demand on the regional economy for national economic recovery due to the Covid-19 pandemic. By 2020, the number of Covid-19 cases in Indonesia is 743,198 cases. On the other hand, Indonesia had an economic contraction in 2020, which is 2.07 percent. From 34 provinces, almost all provinces in Indonesia also had economic contractions. The results showed that the number of Covid-19 cases was significant for value-added in several industrial origins. Using an impact analysis, if there is an economic recovery by increasing total consumption in this significant industrial origin, Indonesia's Gross Domestic Product will increase by 2.74 percent.